Students Variables and the Development of Employability Mastery on Undergraduates Business Education Students in Federal Universities in Southern Nigeria - Cletus Akpo Atah; Basil Nwosu; Emanuel Bessong (Mediterranean Journal of Social Sciences, 2022)
The study examined Students Variables and the development of employability mastery on undergraduates Business Education Students in Federal Universities in Southern Nigeria. Two research questions and two null hypotheses were developed to direct the investigation in order to fulfil the study's objectives. For the study, a survey research design was used. 440 students in their final year of business study made up the population. Data were gathered using a 20-item survey called the "Students Variables and the Development of Employability Mastery' Scale" (SVDEM). Using the Cronbach Alpha statistical method, the instrument's internal consistency was determined, and the result was a 0.95 overall reliability coefficient. In order to analyze the data and provide answers to the study questions, mean (X) and standard deviation (SD) were used. The independent t-test was used to evaluate the null hypotheses at the 0.05 level of significance. The findings from data analysis showed that students’ variables significantly influenced the development of employability mastery with High Influence (HI). While the test of hypotheses revealed that, there is no significant difference in the mean rating of the positive and negative respondents on the influence of students’ attitudes and students’ interest in the development of employability mastery. Based on the study's findings, it was suggested, among other things, that school management should offer opportunities to spark students' interest in vocational courses that will improve their growth of employability mastery before graduation. Received: 26 July 2022 / Accepted: 28 October 2022 / Published: 5 November 2022